Dylematy związane z nadmiernym pobieraniem odsetek. Perspektywa historyczna i teraźniejszość - Czechowska, Iwona (Annales. Etyka w Życiu Gospodarczym, 2013)
The problem of charging interest has been discussed since the time of Aristotle. It was condemned in the Christian religion in the Middle Ages. Only when the interest was specified as a payment for productive capital was it considered that the borrower, enriched by the money lent, should let the lender benefit in accordance with the principle of fairness. The borrower should share the profit with the lender, and from this moment the percentage is no longer something shameful and neglected. Religious beliefs and accepted moral values have changed over time, adapting to the circumstances, so has the approach to collecting interest from the capital lent. However, there is still a great deal of criticism of excessive interest rates. The purpose of this paper is to present a discussion related to the charging of interest presented in the tradition of economics and also to show some aspects of the problem in relation to the present times, such as excessive debt and responsible lending.